Ответы и объяснения

2013-09-25T22:08:49+04:00
№920
a) sqrt[3]{ x^{2} +4x-50}=3
  x^2+4x-50=27  
x^2 +4x-77=0  
D=16+308=324= 18^2
x1= -4+18 / 2=7  
x2= -4-18 / 2=-11  

б)  sqrt[3]{ x^{2} +14x-16}=-4
x^2+14x - 16 = -64
x^22+14ч+48 = 0
D = 196-192=4=2^2
x1 = -14+2 / 2 = -6
x2 = -14-2 / 2 = -8 

№921
a) x + sqrt (3x+7) = 7
sqrt (3x+7) =7-x
3x+7 = (7-x)^2
3x+7 = 49-14x+x^2
x^2 -17x+42 = 0
D = 289 - 168 = 121 = 11^2
x1 = 17+11 / 2 = 14
x2 = 17-11 / 2 = 3

б) sqrt (15 - 3x) -1 = x
sqrt (15 - 3x) = x+1
15-3x = (x+1)^2
15-3x = x^2+2x+1
-x^2-5x+14 = 0
x^2+5x-14 = 0
D = 25+56 = 81 = 9^2
x1 = -5+9/2 = 2
x2 = -5-9/2 = -7